Health-Related Quality of Life of Rural Clients Seeking Telepsychology Services - Kevin R. Tarlow; Carly E. McCord; Timothy R. Elliott; Daniel F. Brossart (International Journal of Telemedicine and Applications)
Sixty million US residents live in rural areas, but health policies and interventions developed from an urban mindset often fail to address the significant barriers to health experienced by these local communities. Telepsychology, or psychological services delivered by distance via technology, is an emerging treatment modality with special implications for underserved rural areas. This study found that a sample of rural residents seeking telepsychology services (n=94) had low health-related quality of life (HRQOL), often due to cooccurring physical and mental health diagnoses including high rates of depression. However, a brief telepsychology treatment delivered to rural clients (n=40) was associated with an improvement in mental health-related quality of life (d = 0.70,  P<.001). These results indicate that despite the complex health needs of these underserved communities, telepsychology interventions may help offset the disparities in health service access in rural areas.